The effect of short-term intensive dynamic psychotherapy (ISTDP) on reducing anxiety, increasing self-empathy, coping and social adaptation in women with the experience of sexual assault - Khatami, Mahyasadat; Sedaghati Fard, Mojtaba (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this research was to determine the effectiveness of short-term intensive dynamic psychotherapy (ISTDP) on reducing anxiety, increasing self-empathy, coping and social adaptation in women who experienced sexual assault. Method: This research was practical in terms of purpose and semi-experimental in terms of method with a pre-test, post-test and follow-up design with a control group. So that two groups of subjects were randomly selected and replaced in two experimental and control groups. In the present study, a statistical population was formed including all women who experienced sexual assault in the year 2020-21 in the counseling and psychology center supporting the art of life in Tehran province. The statistical sample consisted of 30 women who experienced sexual assault, who were selected by available sampling method and then randomly assigned to one of the two experimental (15 people) and control (15 people) groups. Beck's (1988), Mark Davis' (1983) empathy, Lazarus et al.'s (1988) coping, and Clark et al.'s (1953) social adjustment questionnaires were used to collect data. In the following, short-term intensive dynamic psychotherapy (ISTDP) according to the protocol of Abbas (2016) was applied to the experimental group during 15 individual counseling sessions of 90 minutes twice a week, and finally, a post-test was taken from both groups. Analysis of variance with repeated measurements was used in data analysis. Results: The results showed that short-term intensive dynamic psychotherapy reduces anxiety (F=8.95, P